The impact of cardiac loading on a novel metric of left ventricular diastolic function in healthy middle‐aged adults: Systolic–diastolic coupling. Issue 23 (7th December 2021) - MacNamara, James P.; Koshti, Vivek; Dias, Katrin A.; Howden, Erin; Hearon, Christopher M.; Cheng, I‐Jou; Hynan, Linda S.; Levine, Benjamin D.; Sarma, Satyam
Abstract: Aims: Left ventricular (LV) restoring forces are primed by ventricular deformation during systole and contribute to cardiac relaxation and early diastolic suction. Systolic–diastolic coupling, the relationship between systolic contraction and diastolic recoil, is a novel marker of restoring forces, but the effect of left atrial pressure (LAP) is unknown. We tested preliminary methods of systolic–diastolic coupling comparing mitral annular velocities versus excursion distances and hypothesized a recoil/contraction distance ratio would remain unaffected across varying LAP, providing a surrogate for quantifying LV restoring forces. Methods and Results: Healthy subjects ( n = 61, age 52 ± 5 years) underwent manipulation of LAP with lower body negative pressure (LBNP) and rapid normal saline (NS) infusion. Pulmonary capillary wedge pressure (PCWP; pulmonary artery catheter) and tissue Doppler imaging of the mitral annulus were measured. Two models of systolic–diastolic coupling––early diastolic excursion (EDexc )/systolic contraction (Sexc ) distances and e'/systolic (s') velocities were compared. Velocity (e'/s') coupling ratios varied significantly (mean e'/s', slope = 0.022, p < 0.001) in relationship with PCWP (5–20 mmHg). Excursion (EDexc /Sexc ) coupling ratio did not vary in relationship with PCWP (EDexc /Sexc : slope = −0.001, p = 0.19). Conclusions: Systolic–diastolic coupling using mitral annular distance ratios to standardize early diastolic recoil to systolic contraction was not significantly impacted by LAP, in contrast to coupling ratios using velocities. The pressure invariance of annular distance coupling ratios suggests this metric quantifies the efficiency of LV restoring forces by isolating systolic contributions to early diastolic restoring forces independent from changes in LAP. Abstract : Left ventricular restoring forces are primed by ventricular deformation during systole and contribute to cardiac relaxation and early diastolic suction. Systolic–diastolic coupling, the relationship between systolic contraction and diastolic recoil, is a novel and load independent marker of restoring forces. The pressure invariance of the systolic–diastolic distance coupling ratios suggests this metric quantifies the efficiency of LV restoring forces by isolating systolic contributions to early diastolic restoring forces independent from changes in LAP.